Reflections on the integration of a narrative medicine and mindfulness program in hospice and palliative care. (3rd July 2020) - Essary, Alison C.; Lussier, Mark; Stone, Noah; Volk-Craft, Barbara; Hamilton, Gillian
Abstract : By 2060, almost 25% (98 million) of the population is expected to be aged 65 or older. Health care professionals who provide hospice and palliative care are overtasked and demonstrate symptoms of burnout. Narrative medicine and mindfulness interventions create meaningful connections with patients, improve the delivery of patient-centered care, and enhance the health of the caregivers. In this pilot program, health care professionals in hospice and palliative care settings were invited to participate in a study to evaluate the impact of narrative medicine or mindfulness on measures of burnout and empathy. Participants completed baseline and 12-week post-intervention surveys of burnout and empathy, as well as weekly journals of their experience. Mean overall scores for depersonalization were significantly reduced at 12-week post-intervention. There were no significant changes in emotional exhaustion or empathy compared to baseline. This brief, weekly intervention may be beneficial for both patients and health care professionals in the hospice and palliative care setting.